Temperature Control in Polyvinyl Chloride Production: Internal Model Control (IMC) and Proportional, Integral and Derivative (PID) controller Implementation. - Zulkeflee, S.A.; Aziz, N.; Chan, C.K. (2007)

(untitled)
The Polyvinyl Chloride (PVC) suspension polymerization process is an exothermic reaction which is carried out in a batch reactor.